(untitled) (Studia theodisca, 2025)
This article aims to explore the pivotal role of radio drama within the German and Austrian cultural landscape, especially after World War II. Through a comparative and (inter)textual analysis of two central works – Knöpfe (1953) by Ilse Aichinger and Ein Geschäft mit Träumen (1952) by Ingeborg Bachmann – the study traces the origin, development, and impact of this literary genre on the cultural discourse of the post-war context. Additionally, it illustrates the relevance of their common themes in the light of the personal and artistic relationships of the two writers.